Traffic Violations: A Study of Measures Aimed at Bringing Perpetrators to Justice - KHAKIMOV, Yerzhan Maratovich (Journal of Advanced Research in Law and Economics, 2018)
The article is devoted to a study of administrative and legal enforcement actions against violators of road safety (RS) laws used in the Republic of Kazakhstan and some foreign countries. The aim of the present article is to analyze ways of bringing to justice the perpetrators of traffic offences in the national legislation of Kazakhstan and some foreign countries, to assess their effectiveness and the possibility of using foreign experience in the national legal field. The article examines the foreign organizational and legal experience in the application of administrative responsibility for violators of RS laws and the administrative regulations of Kazakhstan; the conclusions have been made, and the recommendations for further improvement of measures to bring to justice violators of RS laws have been given. The author subjects the use of the fine as the main mechanism for bringing to justice perpetrators of the traffic violations to fair criticism. Based on the study of normative materials on administrative law and the experience of foreign countries in counteraction to RS violations, the author suggests ways to eliminate causes and conditions for committing traffic safety violations and formulates the proposals for further improvement of the administrative legislation of the Republic of Kazakhstan, in particular, excluding the prevarication when using the data of photo and video fixation of traffic offences. The main provisions and conclusions of the article can be used in scientific and practical activities in addressing the issues of law violation prevention, the comparative characteristics of the norms of responsibility for RS violations of Kazakhstan and foreign countries laws, and in the subsequent reform of statutory regulations on administrative offences.